Psychological Peculiarities of Styles of Professional Activity and the Level of Stress among Members of Election Commissions in Parliamentary Elections in Ukraine - Лефтеров, Василь Олександрович; Лефтеров, В. О.; Лефтеров, Василий Александрович; Lefterov, Vasyl O.; Lefterov, Vasiliy; Ігнатьєва, Ірина Ігорівна; Ігнатьєва, І. І.; Игнатьева, Ирина Игоревна; Игнатьева, Ирина Игоревна; Ihnatieva, Iryna I.; Ignatieva, Iryna; Приходько, Ігор Іванович; et al. (LUMEN Publishing House, 2021)
The results of the empirical study among the members of election commissions (N=112, age: 25−68 years) for Ukrainian parliamentary elections 2019 to study the styles of their professional activity and the level of stress are presented. The most pronounced style of professional activity is “Professional-perfectionist”, which contributes to the high productivity of members of election commissions. The work tasks at a polling station are best fulfilled by the person with a more pronounced style of professional activity “Formalist-bureaucrat”. It is undesirable to involve working at the polling station persons with high rates in the style of the professional activity of “Nihilist”. It has been found that the major psychological difficulties of working in election commissions are due to excessive psycho-emotional and psychophysical overload, to which some members of the commissions are not ready. This overload can cause them to experience certain mental stress, different levels of stress, their manifestation, and consequences. Although the majority of participants demonstrated a high degree of adaptability to stressful workloads, members of commissions should perform their duties at a highly professional level in extremely difficult circumstances, including at night and in a state of intense emotional stress. The results of the research should be taken into account during the organization of the election process and the holding of elections to central and local authorities. To improve it, it is advisable to organize and conduct early training and skills upgrading of members of election commissions. To do this, it is necessary to develop and implement training programs for the development of style peculiarities of professional activity, which will contribute to effective work in the election commission and overcoming psychological difficulties.

Наведено результати емпіричного дослідження серед членів виборчих комісій (N=112, вік: 25−68 років) на виборах до Верховної Ради України 2019 року щодо вивчення стилів їх професійної діяльності та рівня стресу. Найбільш яскраво вираженим стилем професійної діяльності є «Професіонал-перфекціоніст», що сприяє високій продуктивності роботи членів виборчих комісій. Робочі завдання на виборчій дільниці найкраще виконує особа з більш вираженим стилем професійної діяльності «формаліст-бюрократ». Небажано залучати до роботи на дільниці осіб з високими показниками в стилі професійної діяльності «Нігіліста». Встановлено, що основні психологічні труднощі роботи у виборчих комісіях пов’язані з надмірними психоемоційними та психофізичними перевантаженнями, до яких деякі члени комісій не готові. Це перевантаження може викликати у них певну психічну напругу, різний рівень стресу, їх прояв та наслідки. Незважаючи на те, що більшість учасників продемонстрували високий ступінь адаптивності до стресових навантажень, члени комісій повинні виконувати свої обов’язки на високопрофесійному рівні у надзвичайно складних умовах, у тому числі вночі та в стані сильного емоційного напруження. Результати дослідження необхідно враховувати під час організації виборчого процесу та проведення виборів до органів центральної та місцевої влади. Для їх покращення доцільно організувати та провести дострокове навчання та підвищення кваліфікації членів виборчих комісій. Для цього необхідно розробити та впровадити навчальні програми для розвитку стильових особливостей професійної діяльності, що сприятиме ефективній роботі у виборчій комісії та подоланню психологічних труднощів.
Lefterov V. Psychological Peculiarities of Styles of Professional Activity and the Level of Stress among Members of Election Commissions in Parliamentary Elections in Ukraine / V. Lefterov, I. Ignatieva, I. Prykhodko, O. Timchenko, Yu. Formaniuk, O. Holina // BRAIN. Broad Research in Artificial Intelligence and Neuroscience. - Vol. 12. - Issue 1. – LUMEN Publishing House, 2021. - P. 300-325.
Keywords: parliamentary elections; election commissions; style of professional activity; stress; Ukraine; парламентські вибори; виборчі комісії; стиль професійної діяльності; стрес; Україна; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Psychology